Feed intake of sheep receiving ration with addition of passion fruit peel meal - Aguiar, Sílvia Cristina de; Geron, Luiz Juliano Valério; Nunes, Gabriel Maciel; Garcia, Jocilaine; de Carvalho, Joilma Toniolo Honório; Silva, Ana Paula da (Scientia Agraria Paranaensis, 2020)
Part of the costs of animal production is food, and consequently, several alternatives have been examined for use as co-products, such as passion fruit peel meal (PFP). The objective of this study was to evaluate the dry matter (DMI), nutrient intake, feeding behavior, and physiological parameters of sheep receiving PFP in their ration. Four mixed breed sheep were with a mean body weight of 38.4 kg and distributed in a 4 × 4 Latin square. The experimental diet was formulated with 50% corn silage and 50% concentrate (dry matter [DM] basis), to contain 16% crude protein (CP) and 70% total digestible nutrients, with the addition of PFM to the feed at 0%, 1.6%, 5.8%, and 8.9% based on DMI. The addition of PFP did not affect (P > 0.05) DMI and nutrients, with an average DMI of 838.51 g d-1, 2.21% of body weight, and 54.59 g kg-0.75. The addition of PFP to the ration did not change the feed intake of DM and nutrients. The PFP did not change the ingestive behavior of sheep during the dawn, morning, and afternoon. However, an increase in the intake time and leisure time was observed during the night. PFP did not influence any of the physiological variables; however, the high temperature during the execution of the experiment caused animal discomfort both in the morning and in the afternoon.